Contraception After Delivery and Short Interpregnancy Intervals Among Women in the United States. Issue 6 (June 2015) - White, Kari; Teal, Stephanie B.; Potter, Joseph E.
Abstract : OBJECTIVE: To investigate women's patterns of contraceptive use after delivery and the association between method use and risk of pregnancy within 18 months. METHODS: We used the 2006–2010 National Survey of Family Growth to examine women's contraceptive use after delivery and at 3, 6, 12, and 18 months after giving birth. The sample included 3, 005 births that occurred within 3 years of the survey date and for which information on contraceptive use was available. We estimated multivariable-adjusted Cox regression models to assess the association between women's method use and risk of pregnancy within 18 months after delivery. We also examined the percentage of pregnancies occurring 18 months or less after the index birth that were unintended. RESULTS: Between delivery and 3 months postpartum, contraceptive use increased from 21% to 72%. At 3 months, 13% of women used permanent contraception, 6% used long-acting reversible contraceptives, 28% used other hormonal methods, and 25% relied on less-effective methods; the distribution of method use was similar in subsequent months. Among women using hormonal methods, 12.6% became pregnant within 18 months of delivery or less compared with 0.5% using permanent and long-acting contraception (adjusted hazard ratio [HR] 21.2, 95% confidence interval [CI] 6.17–72.8). Additionally, 17.8% of women using less-effective methods (HR 34.8, 95% CI 9.26–131) and 23% using no method (HR 43.2, 95% CI 12.3–152) became pregnant 18 months or less. At least 70% of pregnancies within 1 year after delivery were unintended. CONCLUSION: Few women use long-acting reversible contraceptives after delivery, and those using less-effective methods have an increased risk of unintended pregnancy. LEVEL OF EVIDENCE: II Abstract : Few U.S. women use long-acting contraceptives in the 18 months after delivery; those using less-effective methods are more likely to get pregnant during this interval.